Pengaruh Pemberian Buah Pepaya Terhadap Kualitas Tidur Anak Prasekolah di Posyandu Bunga Sakura Bekasi Timur - Adli, Rakha Raihan; Bhaktiar, Tri Agung; Trianingsih, Devi; Dinaryanti, Ratna Sari; Rahayu, Diah (PSIK FKKMK UGM, 2026)
Background: The growth and development of preschool children is significantly influenced by adequate sleep quality. Sleep deprivation in children can negatively impact mental and emotional health, as well as physical and cognitive function. Sleep disorders in preschool children are still common, but treatment focuses on pharmacological approaches or behavioral interventions, while the use of natural nutritional interventions has not been widely explored. One intervention method that has the potential to improve sleep quality is the consumption of nutrient-rich natural fruits. Papaya is known to contain active substances that play a role in neurotransmitter regulation and body relaxation. This interest stems from the limited studies on the effect of papaya on sleep quality in preschool children, particularly in the context of pediatric nursing and community care. Objective: This study aimed to determine the effect of papaya on sleep quality in preschool children. Method: This study used a one-group pretest-posttest design. Twenty-two children aged 3 to 5 years with sleep disorders were selected using a purposive sampling technique. The intervention consisted of 200 grams of papaya daily for five consecutive days. Sleep quality was measured using the Children Sleep Habits Questionnaire (CSHQ). Bivariate analysis used the paired t test to examine differences in preschool children's sleep quality scores. Results: The study showed a significant improvement in sleep quality after the intervention, with pre- and post-intervention scores (83,50±8,07 and 40,18±4,03 respectively). The bivariate test yielded a p-value of <0,05. Conclusion: Papaya fruit has been shown to be effective in improving preschool children's sleep quality scores. This intervention can be used as a safe and effective natural alternative to address children's sleep disorders.INTISARILatar belakang: Permasalahan gangguan tidur pada anak prasekolah masih sering ditemukan, namun penanganan yang dilakukan masih berfokus pada pendekatan farmakologis atau intervensi perilaku, sementara pemanfaatan intervensi nutrisi alami belum banyak dieksplorasi. Salah satu metode intervensi yang berpotensi meningkatkan kualitas tidur adalah konsumsi buah-buahan alami yang kaya nutrisi seperti Pepaya yang diketahui mengandung zat aktif dalam regulasi neurotransmitter dan relaksasi tubuh. Studi tentang manfaat Pepaya dalam meningkatkan kualitas tidur masih terbatas khususnya pada konteks keperawatan anak dan komunitas. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh pemberian buah Pepaya terhadap kualitas tidur anak usia prasekolah. Metode: Penelitian ini menggunakan one group pretest-posttest design. Sebanyak 22 anak berusia 3 hingga 5 tahun yang mengalami gangguan tidur dipilih menggunakan teknik purposive sampling. Intervensi berupa pemberian buah Pepaya sejumlah 200 gram setiap hari selama lima hari berturut-turut. Kualitas tidur diukur menggunakan instrumen Children Sleep Habits Questionnaire (CSHQ). Analisis bivariat menggunakan uji paired t test untuk melihat perbedaan skor kualitas tidur anak prasekolah. Hasil: Hasil penelitian menunjukkan adanya peningkatan kualitas tidur yang signifikan setelah intervensi dengan nilai pretest 83,50 ± 8,070 dan posttest 40,18 ± 4,03. Hasil uji bivariat didapatkan nilai p sebesar 0,000 (p-value < 0,05). Simpulan: Buah Pepaya terbukti efektif meningkatkan skor kualitas tidur anak usia prasekolah. Intervensi ini dapat digunakan sebagai alternatif alami yang aman dan efektif untuk mengatasi gangguan tidur anak.